China's Expanding Role in Global Mergers and Acquisitions Markets - Wolf, Jr (RAND Corporation, 2011)
The authors evaluate the risks and benefits of increased Chinese foreign investment, aiming to improve understanding of its investment patterns and strategy. They consider how U.S. national security might be compromised as well as how the United States and China can benefit from such investment, providing a way to assess national security risks and benefits and examining Chinese investment patterns in both the United States and elsewhere.